Love Tragedy, She Wrote - Esa, Mohd Shah Mat; Othman, Zahiruddin; Yaacob, Mohd Jamil (Penerbit USM, 2004)
This case report is unique because it entails special talent from a psychiatric patient. As an intelligent and talented writer, this patient used to correspond with her therapist (the first author) via letters to express her thought and to ventilate her emotion. Those letters were studied by his supervisor (the second author) and blindly analyzed by the third author. The letters were seen as reflection of the patient’s mental states over the years. The conclusions were made based on collective opinions of all quarters to avoid bias and to construct a clinically justified opinion.